2022
DOI: 10.3390/pathogens11010053
|View full text |Cite
|
Sign up to set email alerts
|

Neofusicoccum mediterraneum Is Involved in a Twig and Branch Dieback of Olive Trees Observed in Salento (Apulia, Italy)

Abstract: Olive trees are infected and damaged by Botryosphaeriaceae fungi in various countries. The botryosphaeriaceous fungus Neofusicoccum mediterraneum is highly aggressive and is a major concern for olive groves in Spain and California (USA), where it causes ‘branch and twig dieback’ characterized by wood discoloration, bark canker, and canopy blight. During surveys of olive groves in Apulia (southern Italy), we noticed that—in some areas—trees were heavily affected by severe branch and twig dieback. In addition, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Phillips, a fungal species previously reported in California and Spain as the causal agent of severe Branch and Twig Dieback (BTD) of olive trees [ 9 , 11 , 13 ]. Indeed, the pathogenicity trials performed with the Apulian isolate clearly showed the high aggressiveness of this species and its capacity to reproduce the observed symptomatology, confirming what had been previously reported for this species [ 11 , 13 , 22 ].…”
Section: Introductionsupporting
confidence: 87%
See 4 more Smart Citations
“…Phillips, a fungal species previously reported in California and Spain as the causal agent of severe Branch and Twig Dieback (BTD) of olive trees [ 9 , 11 , 13 ]. Indeed, the pathogenicity trials performed with the Apulian isolate clearly showed the high aggressiveness of this species and its capacity to reproduce the observed symptomatology, confirming what had been previously reported for this species [ 11 , 13 , 22 ].…”
Section: Introductionsupporting
confidence: 87%
“…Previously, during a survey in an olive orchard located in the municipality of Mesagne (Brindisi province, Apulia, southern Italy), we found olive trees severely affected by BTD. Regarding this phytopathological case, we published a first study focused on the characterization of N. mediterraneum , a botryosphaeriaceous fungus that turned out to be strongly involved in the disease [ 22 ]. In the present study, we focused on additional Botryosphaeriaceae -like isolates, different from N. mediterraneum , which were also found associated with BTD in that survey (CREA-DC TPR OL.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations